Vomiting and Dysphagia Predict Delayed Gastric Emptying in Diabetic and Nondiabetic Subjects. (11th May 2014) - Boltin, Doron; Zvidi, Ibrahim; Steinmetz, Adam; Bernstine, Hanna; Groshar, David; Nardi, Yuval; Boaz, Mona; Niv, Yaron; Dickman, Ram
Abstract : Background. Gastroparesis is a heterogeneous disorder most often idiopathic, diabetic, or postsurgical in nature. The demographic and clinical predictors of gastroparesis in Israeli patients are poorly defined. Methods. During the study period we identified all adult patients who were referred to gastric emptying scintigraphy (GES) for the evaluation of dyspeptic symptoms. Of those, 193 patients who were referred to GES from our institution were retrospectively identified (76 (39%) males, mean age 60.2 ± 15.6 years). Subjects were grouped according to gastric half-emptying times (gastric T 1 / 2 ). Demographic and clinical data were extracted from electronic medical records or by a phone interview. Key Results. Gastric emptying half-times were normal (gastric T 1 / 2 0–99 min) in 101 patients, abnormal (gastric T 1 / 2 100–299 min) in 67 patients, and grossly abnormal (gastric T 1 / 2 ≥ 300  min) in 25 patients. Vomiting and dysphagia, but neither early satiety nor bloating, correlated with delayed gastric emptying. Diabetes was associated with grossly abnormal gastric T 1 / 2 . Idiopathic gastroparesis was associated with a younger age at GES. No correlation was observed between gastric T 1 / 2 values and gender, smoking, H. pylori infection, HBA1C, or microvascular complication of diabetes. Conclusions Inferences. Vomiting and dysphagia are predictive of delayed gastric emptying in both diabetic and nondiabetic subjects. Diabetes is associated with more severe gastroparesis.